2022
DOI: 10.3390/su14063588
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Relationships among the Key Factors Affecting the Performance of Coal-Fired Thermal Power Plants: Implications for Achieving Clean Energy

Abstract: Most countries depend on coal-fired thermal power plants (CTPPs) to meet energy demands. However, the adverse environmental impacts of CTPPs also remain a major concern. As the energy generations from renewable energy resources are still in the developing stage, reliance on CTPPs is inevitable. Hence, the efficiency of CTPPs has to be improved, while decreasing carbon emissions. This study aims to identify and evaluate the key factors that need to be addressed in improving the performance and minimizing the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…As GSC has been assisted by Internet usage, helps to minimize harmful emissions and optimizes the response time (Mastos et al, 2021). Recent studies reported that the deficiency of modern technologies is the main hurdle in the implementation of circular economic activities (Sivageerthi et al, 2022). However, the use of I4 technologies also helped in decreasing the production waste as well as led to boost up consumption efficiency.…”
Section: Industry 40 and Green Supply Chain Managementmentioning
confidence: 99%
“…As GSC has been assisted by Internet usage, helps to minimize harmful emissions and optimizes the response time (Mastos et al, 2021). Recent studies reported that the deficiency of modern technologies is the main hurdle in the implementation of circular economic activities (Sivageerthi et al, 2022). However, the use of I4 technologies also helped in decreasing the production waste as well as led to boost up consumption efficiency.…”
Section: Industry 40 and Green Supply Chain Managementmentioning
confidence: 99%
“…This leads to 80,000 to 115,000 premature deaths and 20 million asthma cases. Another recent study [22] suggests that 32% of global chronic respiratory disease occurs in India. The disposal of coal ash into the environment exposes the communities to heavy metals and particulate matter waste.…”
Section: Coal Thermal Power Plants In Indiamentioning
confidence: 99%